Relative bioavailability of iron from organic sources for weanling piglets - Luiggi, Fabiana Golin [UNESP]; Berto, Dirlei Antonio [UNESP]; Mello, Gabriela de [UNESP]; Carneiro Girão, Lucio Vilela [UNESP]; Ensá Junqueira Villela, Cássio Cordeiro [UNESP]; Lo Tierzo, Vivian [UNESP]; Amorim, Alessandro Borges [UNESP]; Trindade Neto, Messias Alves da (Univ Estadual Londrina, 2014)
Some authors consider minerals from organic sources more bioavailable for pig nutrition in comparison with inorganic sources. To evaluate the relative iron bioavailability from the organic source iron carbo-amino-phospho-chelate (ICAPC) to weanling piglets, it was conducted an experiment with 126 commercial piglets, using iron sulfate monohydrate (S) as standard. The experiment had a randomized block design with seven treatments (diet without adding specific source of iron, diet with 50, 100 and 150 ppm iron from S and diet with 50, 100 and 150 ppm iron from ICAPC), six replications and three animals per experimental unit. Performance parameters (average daily gain - ADG, feed: gain ratio - F:G) and blood variables (hemoglobin - Hb, hematocrit - Ht, transferrin - TR, latent iron-binding capacity - LIBC, total iron-binding capacity - TIBC, serum iron - Fe and transferrin saturation index - TSI) were evaluated. At the end of the experiment a piglet from each experimental unit was slaughtered and its liver and spleen removed for assessment of iron concentration by flame atomic absorption spectrometry (FAAS). The evaluated sources of iron yielded similar results for the variables of interest, but the increase in iron intake was followed by a linear increase in ADG, Hb, Ht, Fe and TSI as well as a linear decrease in the values of F:G, TR, LIBC and TIBC. Iron bioavailabilities from both ICAPC and S sources are similar for weanling piglets.

Alguns autores consideram os minerais de fontes orgânicas mais biodisponíveis para a nutrição de suínos quando comparados à minerais de fontes inorgânicas. Para avaliar a biodisponibilidade relativa do ferro proveniente da fonte orgânica carbo-amino-fosfo-quelato de ferro (CAFQF), foi conduzido um experimento com 126 leitões de linhagem comercial, utilizando o sulfato de ferro (S) como padrão. O delineamento experimental foi inteiramente casualizado com sete tratamentos (dieta sem adição de fonte específica de ferro, dietas com 50, 100 e 150 ppm de ferro na forma de S e dietas com 50, 100 e 150 ppm de ferro na forma de CAFQF), seis repetições e três animais por unidade experimental. Parâmetros de desempenho (ganho de peso médio diário – GMD, conversão alimentar – CA) e variáveis sanguíneas (hemoglobina – Hb, hematrócrito – Ht, transferrina – TR, capacidade latente de ligação do ferro – CLLF, capacidade total de ligação do ferro – CTLF, ferro sérico – FS e índice de saturação da transferrina – IST) foram avaliados. Ao final do experimento um leitão por unidade experimental foi abatido para a retirada do fígado e braço para avaliação da concentração de ferro por espectrometria de absorção atômica em chama (FAAS). As fontes de ferro avaliadas apresentaram resultados semelhantes para as variáveis de interesse, mas o aumento da ingestão de ferro resultou em aumento linear nos valores de GMD, Hb, Ht, FS e IST e redução linear nos valores de CA, TR, CLLF e CTLF. Para leitões desmamados a biodisponibilidade do ferro proveniente do CAFQF é similar à do S.
Biodisponibilidade relativa do ferro de fonte orgânica para leitões desmamados
Keywords: Chelated mineral; Hemogram; Iron deficiency anemia; Nutrition; Swine; Anemia ferropriva; Hemograma; Mineral quelatado; Nutrição; Suínos